Упростите выражение (a+2)(a-3)-(4-a)(a+4)

0 голосов
40 просмотров

Упростите выражение (a+2)(a-3)-(4-a)(a+4)


Алгебра (30 баллов) | 40 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

(a+2)(a-3)-(4-a)(a+4) = (a^2+2a-3a-3*2)-(4^2-a^2) =
= a^2+2a-3a-6-16+a^2 = 2a^2-a-22

(5.5k баллов)
0

cgfcb,j

0

спасибо)

0

а что такое [/tex]

0

это припррописке формул бывает. Сейчас же в тексте не видно?

0

всё хорошо теперь

0

спасибо

0 голосов

(a+2)(a-3)-(4-a)(a+4)=a²-3a+2a-6-4(4-a)*(4+a)=a²-3a+2a-6-(16-a²)=a²-3a+2a-6-16+a²=2a²-a-22